Recobrimento de sementes de arroz irrigado com zinco - Funguetto, Claudete Izabel (2006)
The objective of this research was to evaluate the response of irrigated rice cultivars BRS 7 Taim and IRGA 417 to seed coating with micronutrient, fungicide and polymer. The experiment was conducted in laboratory and in greenhouse conditions. Seed treatment was done using a mixture of Zn sulphate heptahydrated (pure formulation) + 3.0 mL carboxim + thiram fungicides + 200 mg CF Clear ® polymer + 4.0 mL color + 15 mL of water.kg -1 of seed. Dosage of micronutrient tested were zero; 0.37; 0.47; 0.57; 0.67 e 0.77 g/Zn.kg -1 of seeds. Seed quality evaluations were done through the following tests: standard germination; first count of germination; length of aerial and root parts and dry biomass of aerial and root parts of seedlings; number of panicles per plant; number of grains per panicle and grain weight per plant. Statistical design was completely randomize wit three replications. Results showed that seed coating with micronutrient Zn, fungicide and polymer did not adversely affect germination of irrigated rice, it was different between cultivars and shows high correlation for most analyzed parameters and for germination under sub-optimal temperature conditions. Number of grains per panicle and weight of grains per plant were positively correlated with Zn dosage, providing increase in production. It is possible to conclude that seed coating wit micronutrient Zn, fungicide carboxim + thiram and polymer CF Clear ® may be feasible.